Climate vulnerability assessment and development of adaptation strategies for agricultural value chains in Nampula and Zambézia, Mozambique - Mwungu, Chris; Osiemo, Jamleck; Koech, Grace; Majambo, Gamoyo; Chege, Christine; Binge, Brenda; Chilambe, Pedro (2025)
Mozambique is increasingly vulnerable to climate risks, particularly in its agricultural sector, with the northern provinces of Nampula and Zambézia being particularly affected. Over recent decades, recurring droughts, floods, cyclones, and temperature extremes have worsened, threatening rural livelihoods, food security, and the stability of agricultural value chains. This report presents a comprehensive climate vulnerability assessment and proposes adaptation strategies for key value chains, including cassava, groundnuts, maize, sesame, cattle, goats, rice, tobacco, and sugarcane, across these provinces. The findings highlight the urgent need for localised data to guide resilience initiatives, especially in areas where poverty, infrastructure gaps, and reliance on rain-fed farming increase climate risks. The study employs the IPCC vulnerability framework, combining exposure, sensitivity, and adaptive capacity indicators to develop district-specific vulnerability indices. It utilises high-resolution climate data, biophysical datasets, socioeconomic indicators, and value chain diagnostics. These indicators are standardised and combined into a composite index, which helps in mapping the spatial distribution of climate hazards and socio-economic vulnerabilities. Moreover, a value chain approach is employed to analyse climate risks across the stages of input procurement, on-farm production, post-harvest handling, marketing, and consumption. This integrated analysis provides a comprehensive view of how climate stress spreads through agricultural systems. Findings reveal notable spatial variations in climate vulnerability. Zambézia demonstrates a higher overall risk, particularly in districts such as Milange and Morrumbala, which score highest due to a combination of moderate-to-high exposure, heightened sensitivity, and limited adaptive capacity. Nampula appears relatively less vulnerable, with several districts benefiting from improved market access and productivity. However, both provinces face systemic challenges, including limited climate information, inadequate infrastructure, and farmers constrained financial resources. Drought remains the most common climate hazard across all evaluated value chains. To build climate resilience in Nampula and Zambézia, integrated, context-specific approaches are essential, encompassing technical, institutional, and policy measures. Boosting adaptive capacity through investments in extension services, climate-resilient infrastructure, inclusive innovation systems, and multi-stakeholder partnerships is vital for safeguarding rural livelihoods and ensuring the long-term sustainability of Mozambique's agriculture.